2000
DOI: 10.1063/1.126754
|View full text |Cite
|
Sign up to set email alerts
|

High quality Ge on Si by epitaxial necking

Abstract: We show that pure Ge grown selectively on SiO2/Si substrates in 100 nm holes is highly perfect at the top surface compared to conventional Ge lattice-mismatched growth on planar Si substrates. This result is achieved through a combination of interferometric lithography SiO2/Si substrate patterning and ultrahigh vacuum chemical vapor deposition Ge selective epitaxial growth. This “epitaxial necking,” in which threading dislocations are blocked at oxide sidewalls, shows promise for dislocation filtering and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
136
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(137 citation statements)
references
References 21 publications
0
136
0
1
Order By: Relevance
“…8 Another approach is to deposit Ge directly on Si substrate and then introduce annealing step during and/or after the Ge growth to reduce the TDD. [9][10][11][12][13][14][15] However, this approach results in a much higher TDD of >10 7 cm −2 (Refs. [16][17][18] and severe Si/Ge inter-mixing at the in growth interface.…”
Section: 6mentioning
confidence: 99%
“…8 Another approach is to deposit Ge directly on Si substrate and then introduce annealing step during and/or after the Ge growth to reduce the TDD. [9][10][11][12][13][14][15] However, this approach results in a much higher TDD of >10 7 cm −2 (Refs. [16][17][18] and severe Si/Ge inter-mixing at the in growth interface.…”
Section: 6mentioning
confidence: 99%
“…It has been shown that the high aspect ratio of the STI trench can be used to trap the defects at the bottom of the trench and the STI sidewalls. 2,[16][17][18][19] In this case, a single SiGe layer is used as virtual substrate. This aspect ratio trapping typically works well perpendicular to the trench, but along the trench innovations in epitaxial growth are needed to reduce the number of defects.…”
mentioning
confidence: 99%
“…Previous reports have demonstrated that the defect necking effect is limited to trenches with aspect ratio (depth to width) greater than 2 [7,9,10]. pMOS device performance boost on Ge selectively grown in STI trenches has been demonstrated recently [11].…”
Section: Introductionmentioning
confidence: 99%
“…One approach to integrate these materials on Si substrates is SAG in shallow trench isolated (STI) structures [5,6]. Using this approach, it should be possible to obtain extended defect free areas by the so-called defect necking effect [7]. This would enable an alternative route for making III-V channel nMOS devices.…”
Section: Introductionmentioning
confidence: 99%